α-Tocopherol disappearance rates from plasma depend on lipid concentrations: studies using deuterium-labeled collard greens in younger and older adults - Traber, Maret G; Leonard, Scott W; Bobe, Gerd; Fu, Xueyan; Saltzman, Edward; Grusak, Michael A; Booth, Sarah L (The American journal of clinical nutrition, 2015)
Background: Little is known about α-tocopherol’s bioavailability as a constituent of food or its dependence on a subject’s age. Objective: To evaluate the α-tocopherol bioavailability from food, we used collard greens grown in deuterated water (²H collard greens) as a source of deuterium-labeled (²H) α-tocopherol consumed by younger and older adults in a post hoc analysis of a vitamin K study. Design: Younger (mean ± SD age: 32 ± 7 y; n = 12 women and 9 men) and older (aged 67 ± 8 y; n = 8 women and 12 men) adults consumed a test breakfast that included 120 g ²H collard greens (1.2 ± 0.1 mg ²H-α-tocopherol). Plasma unlabeled α-tocopherol and ²H-α-tocopherol were measured by using liquid chromatography–mass spectrometry from fasting (>12 h) blood samples drawn before breakfast (0 h) and at 24, 48, and 72 h and from postprandial samples collected at 4, 5, 6, 7, 9, 12, and 16 h. Results: Times (12.6 ± 2.5 h) of maximum plasma ²H-α-tocopherol concentrations (0.82% ± 0.59% total α-tocopherol), fractional disappearance rates (0.63 ± 0.26 pools/d), half-lives (30 ± 11 h), and the minimum estimated ²H-α-tocopherol absorbed (24% ± 16%) did not vary between age groups or sexes (n = 41). Unlabeled α-tocopherol concentrations were higher in older adults (26.4 ± 8.6 μmol/L) than in younger adults (19.3 ± 4.2 μmol/L; P = 0.0019) and correlated with serum lipids (r = 0.4938, P = 0.0012). In addition, ²H-α-tocopherol half-lives were correlated with lipids (r = 0.4361, P = 0.0044). Conclusions: Paradoxically, α-tocopherol remained in circulation longer in participants with higher serum lipids, but the ²H-α-tocopherol absorbed was not dependent on the plasma lipid status. Neither variable was dependent on age. These data suggest that plasma α-tocopherol concentrations are more dependent on mechanisms that control circulating lipids rather than those related to its absorption and initial incorporation into plasma. This trial was registered at clinicaltrials.gov as NCT0036232.